"I was In Prison and You Visited Me" Providing Pastoral Care to Detained Young Latinos. (March 2021) - Krogsrud, Silvana
This Article offers strategies for providing comprehensive pastoral care to detained young Latinos. Strategies include Clinebell's five functions of pastoral care, listening skills, and creative writing. Also discussed are the specific circumstances leading to the detention of juvenile Latino offenders.